Prospects for the use of sulfur-containing pteridines in toxic liver damage - Lohvinenko, N.; Shvets, V. M.; Berest, G. H.; Nosulenko, I. S.; Voskoboinik, O.; Severina, H.; Okovytyy, S.; Kovalenko, S.; Швець, Володимир Миколайович; Берест, Галина Григорівна; Носуленко, Інна Степанівна (My University, 2024)
The presented material describes the results of the purposeful search for the novel hepatoprotective agents among synthetic sulfur-containing pteridines. The studied compounds were obtained using previously described synthetic procedures. SwissADME and ProTox-II services, as well as a docking study were used to predict the compounds` pharmacokinetics, drug-likeness and toxicity. The effects of sulfur-containing pteridines on lipid peroxidation in vitro and GSH/GSSG levels in vivo were studied for evaluation of their hepatoprotective potential. In silico procedures allowed us to exclude the compounds with inappropriate ADME parameters and high predicted toxicity. Molecular docking of the obtained compounds towards the active site of CYP-enzyme allowed us to clarify the specifics of ligand-enzyme interactions and predict cytochrome-inhibiting activity of the studied agents. The antioxidant activity of the studied compounds was evaluated in vitro using the linoleic acid peroxidation model. It has been found that sulfur-containing pteridines inhibit the peroxidation of linoleic acid. The structure – antioxidant activity relationships were evaluated and discussed as well. Additionally, it has been estimated that antioxidant properties of the studied pteridines directly correlate with their hydrophilicity and number of functional groups with exchangeable proton in molecules. In vivo studies showed that some of the studied sulfur-containing pteridines reduced severity of the hepatotoxic effects caused by the administration of carbon tetrachloride. (3-(7-Hydroxy-4-oxo-2-thioxo-1,2,3,4-tetrahydropteridin-6-yl)propanoyl)alanine has been identified as the most active hepatoprotective agent. The above mentioned compound significantly increases the content of GSH and decreases the level of GSSG compared with non-treated experimental pathology, which reliably affirms its hepatoprotective activity. The hepatoprotective activity of the studied compounds is likely associated with their ability to increase the level of GSH, inhibit lipid peroxidation and decrease prooxidant compounds levels. The obtained results attest the reasonability of further search for hepatoprotective agents among sulfur-containing pteridine derivatives.
Keywords: pteridines; inhibition of linoleic acid peroxidation; determination of glutathione in liver homogenate; hepatoprotective activity; free-radical scavenging activity; tetrachloromethane hepatitis in rats